Towards a Progressive Fatwa: MUI's Response to the COVID-19 Pandemic - M. Asrorun Ni’am Sholeh (Universitas Islam Negeri Jakarta, 2020)
This study examines the Fatwās issued by the Indonesian Ulama Council (Majelis Ulama Indonesia/MUI) on Indonesian Muslim attitudes and practical procedures towards their religious behaviors and public demands on the government appreciation and recognition. The fatwās present logical reasoning which has attracted the government’s attention to adopting them and issue legal products based on them. With a normative legal research approach, this study is considered as qualitative research which using critical legal theory to analyze the important points in the Fatwās. As a result, this study finds four important cases in the fatwā on religious attitudes and behaviors during the COVID-19 pandemic: first, the fatwa on COVID-19 has logical reasoning which is in line with paramedical advice; second, the fatwa on COVID-19 is consistent with the government political interests concerning physical and social restrictions; third, the fatwa on COVID-19 ends the negative stigma on the political role of religious actors; and fourth, the fatwa shows the increasing role of Kiai (religious figures) from cultural brokers to actors of Islamic legal scientism. AbstrakPenelitian ini menguji fatwā hukum yang dikeluarkan oleh Majelis Ulama Indonesia (MUI) tentang sikap dan prosedur praktis umat Islam Indonesia dalam beragama serta tuntutan publik atas penghargaan dan pengakuan pemerintah. Fatwā tersebut menghadirkan nalar logis sehingga menarik perhatian pemerintah untuk mengadopsi dan mengeluarkan produk hukum yang didasarkan pada fatwā tersebut. Dengan pendekatan penelitian hukum normatif, penelitian kualitatif ini menggunakan teori hukum kritis untuk menganalisis poin-poin penting dalam fatwā. Hasilnya, studi ini menemukan empat kasus penting dalam fatwā tentang sikap dan perilaku beragama selama pandemi COVID-19. Pertama, fatwā hukum tentang COVID-19 memiliki penalaran logis yang sejalan dengan nasihat paramedis; kedua, fatwā hukum tentang COVID-19 sejalan dengan kepentingan politik pemerintah mengenai pembatasan fisik dan sosial; ketiga, fatwā hukum tentang COVID-19 mengakhiri stigma negatif terhadap peran politik aktor agama; dan keempat, fatwā hukum menunjukkan semakin meningkatnya peran kiai dari calo budaya menjadi pelaku ilmu hukum Islam.